Religion and Politics in a Global Society : Comparative Perspectives from the Portuguese-Speaking World. - Manuel, Paul Christopher (Lexington Books, 2012)
Religion and Politics in a Global Society: Comparative Perspectives from the Portuguese Speaking World, edited by Paul Christopher Manuel, Alynna Lyon, and Clyde Wilcox, explores the legacy of the Portuguese colonial experience, with careful consideration of the lasting impression that this experience has had on the cultural, religious, and political dynamics in the former colonies.